2000
DOI: 10.1063/1.1308268
|View full text |Cite
|
Sign up to set email alerts
|

A new method for searching for free fractional charge particles in bulk matter

Abstract: A new method to calculate the beam charge for an integrating current transformer Rev. Sci. Instrum. 83, 093302 (2012);

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…We have demonstrated that the piezoelectric liquid drop generation technique, originally used for searching for free fractional charge particles in liquids [30,32], The interval corresponds to thousands of high voltage pulses (consistent with the "inverse logarithmically slow" density relaxation in a vibrated granular material discussed for instance in [39,40]) and the clot generation process resembles water dripping from a slightly open tap. The most puzzling question that remains is the origin of forces which bind the powder particles in the clot.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have demonstrated that the piezoelectric liquid drop generation technique, originally used for searching for free fractional charge particles in liquids [30,32], The interval corresponds to thousands of high voltage pulses (consistent with the "inverse logarithmically slow" density relaxation in a vibrated granular material discussed for instance in [39,40]) and the clot generation process resembles water dripping from a slightly open tap. The most puzzling question that remains is the origin of forces which bind the powder particles in the clot.…”
Section: Discussionmentioning
confidence: 99%
“…The design of the piezoelectric droplet generator used in our experiment has been described in detail elsewhere [31,32]. The dropper consists of a pipette- …”
Section: Experimental Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of the piezoelectric droplet generator used in our experiment has been described in detail elsewhere [31,32] We found that the dropper operation with dry powder significantly differs from the original drop-on-demand regime where a liquid drop is generated at each high voltage pulse. In our experiment, a clot is generated quasi-periodically with many pulses necessary to produce one clot, and with a strong ejection dependence on the pulse repetition frequency.…”
Section: Experimental Approachmentioning
confidence: 99%
“…Given a known radius from the vertical terminal velocity measurement, the charge of the drop can be calculated from the lateral terminal velocity and the value of the electric field [6,7,8]: …”
Section: Horizontal Electric Fieldmentioning
confidence: 99%